Natural anti–malarials: A bright hope - Shoeb Ahmad; G G H A Shadab; Nuzhat Parveen (International Journal of Phytomedicine, 2013)
Malaria is still an ever–continuing epidemic that claims a large number of lives in tropical and subtropical regions of the globe. The alarming rate at which the parasite, Plasmodium has developed resistance to currently used anti–malarial drugs makes it imperative to search for newer and more effective therapeutic agents. In this context, during last few decades several fundamental researches have been conducted to explore novel anti–malarial formulations. However, recent scientific evidences have indeed demonstrated that a variety of plant compounds may check the survival of Plasmodium both in vitro and in vivo. But, there is a need to evaluate and advocate their efficiency in a proper way, because reliable data on the clinical pharmacology and safety of such formulae are extremely scarce, preventing a responsible consideration of their potential benefits. Conclusively, after reviewing literatures it is very clear that plants with anti–malarial activity do not have fully defined this therapeutic property. Therefore, it is necessary to encourage multidisciplinary and interdisciplinary research, mostly those related to natural products enabling the discovery of new and appropriate anti–malarial pharmaceuticals.